Controlled decomposition of SF6 by electrochemical reduction - Bouvet, Sébastien; Pégot, Bruce; Sengmany, Stéphane; Le Gall, Erwan; Léonel, Eric; Goncalves, Anne-Marie; Magnier, Emmanuel (Beilstein Journal of Organic Chemistry, 2020)
The electroreduction of SF6 is shown at ambient temperature in acetonitrile using an array of platinum microelectrodes to improve the electrical detection. Its half reduction potential occurs at −2.17 V vs Fc+/Fc. The exact number of electrons for the full consumption of sulfur hexafluoride was determined and this gas further quantitatively transformed into environmentally benign fluoride anion and sulfur by electrochemical reduction.
Keywords: electroreduction; fluoride anion; redox potential; sulfur hexafluoride